TOWARDS AN EQUITABLE AND LIBERAL SOCIETY: 20TH CENTURY LITERARY CRITICISM AND THEORIES - Kaur, Manjit (PEOPLE: International Journal of Social Sciences, 2019)
Literature attains its academic value when assessed through the tools offered by literary theories and tradition of past and present. The very word ‘theories’ may sound abstract and reductive by nature if understood in the postmodern sense but given their technical/academic means and measures accumulated over a period of time based on the philosophical and ideological concepts, they pave a way for identifying the emotional and social conflicts in the changing socio and cultural scenario of the societies. The present paper focuses on the 20th century Literary theories beginning from Deconstruction associated with Jacques Derrida ranging across Post structuralism, Post colonialism and New Leftist Cultural Theories of Raymond Williams in their attempt to highlight their empowering aspect of dealing with the hierarchical elements of society based on gender, class and ethnicities. The paper finds its relevance in the current globalised, capitalist and consumerist society that tends to ignore the difference or the presence of small voices, as of the marginalized group- be it women Blacks, Asians, Dalits or the poor. The hierarchical structures embedded in the society as human constructs and hegemony as something to be understood and tackled are the main focus of the literary theories discussed in the paper.